2017
DOI: 10.1177/1060028017699635
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Guideline Evidence for Off-label Medication Use in the Intensive Care Unit

Abstract: Because more than half of off-label medication use has the benefit of supportive guidelines recommendations and a majority of gradings are inconsistent with DRUGDEX, clinicians should consider utilizing guidelines to inform off-label medication use in the ICU. Still, there is a considerable amount of off-label medication use in the ICU that lacks supporting evidence, and use remains concerning because it may lead to inappropriate treatment and adverse events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 115 publications
1
5
0
1
Order By: Relevance
“…The most prescribed therapeutic class in the off-label use of drugs was systemic antimicrobials (14.44%), which corroborates studies performed in ICUs of American hospitals (17%) (Shoulders et al, 2017). Lat et al (2011) indicated that the low number of drugs approved by the FDA for treatment of sepsis is a major reason for the off-label use of antimicrobial drugs.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The most prescribed therapeutic class in the off-label use of drugs was systemic antimicrobials (14.44%), which corroborates studies performed in ICUs of American hospitals (17%) (Shoulders et al, 2017). Lat et al (2011) indicated that the low number of drugs approved by the FDA for treatment of sepsis is a major reason for the off-label use of antimicrobial drugs.…”
Section: Discussionsupporting
confidence: 79%
“…The term "off-label" refers to the prescribing and administration of drugs in a different manner to that described in package inserts with regard to factors such as the age of the patient, therapeutic indication, dosage, and frequency (Aronson, Ferner, 2017;Shoulders et al, 2017). In some hospital units, such as oncology, pediatrics, and intensive care, the use of drugs for unapproved indications and/or dosages is common, probably due to the lack of comprehensive clinical studies in these fields (Smithburger et al, 2015;Casañ et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the situation for adult off‐label prescribing appears more favorable. In the intensive care setting, off‐label drug use was supported by high to moderate quality evidence, defined as level A1, A2 or B, in 64% of the cases, 25 compared with only 34% in our study. In adult oncology patients, 61% of off‐label prescriptions were supported by at least well designed non‐RCTs 26 …”
Section: Discussionmentioning
confidence: 50%
“…7 Não há estudos na literatura evidenciando efetividade e segurança do uso prolongado da solução injetável de tartarato de metoprolol. 8 A literatura consultada recomenda a administração por sonda desde que seja realizada preparação de forma adequada (uso de cabine de segurança biológica e de equipamentos de proteção individual) para reduzir risco ao manipulador. 9 Água destilada (AD).…”
Section: Figuraunclassified